Desempeño exportador de las KIBS desde una perspectiva de innovación, digitalización y bases de conocimiento diferenciado: evidencias desde Perú - Castro, René (2022)
The study analyzes the export performance of Peruvian KIBS in terms of their digitization, innovation results and knowledge bases differentiated by KIBS subsectors (technological, professional and creative). Different non-linear probability logit models were estimated using the 2019 National Business Survey. It was verified that, among digital capabilities, only those associated with productive uses of ICTs were found to have a positive relationship with export performance, as well as organizational innovation. However, when considering KIBS subsectors with different knowledge bases, it is observed that innovation has heterogeneous results on export performance regardless of the inclusion of digitization as a determinant. The findings suggest for policy design to consider that there are particular drivers of innovation in certain KIBS subsectors.